Answer:
x = 5t - a
Explanation:
The problem deals with making a variable the subject of the formula in the expression.
Given expression:
6x + a = 5(x + t)
We are to make x the subject of the formula in the expression
Solution:
6x + a = 5(x+t)
On the right hand side, expand the parentheses and distribute the term outside;
6x + a = 5x + 5t
Bring the term desired to be the subject to one side by adding (-5x) to both sides;
6x + (-5x) + a = 5x + (-5x) + 5t
x + a = 5t
Now add (-a) to both sides
x + a + (-a) = 5t + (-a)
x = 5t - a